The optimal supply of central bank reserves under uncertainty - Gara Afonso; Gabriele La Spada; Thomas Mertens; John C. Williams (Federal Reserve Bank of New York, 2023)
This paper provides an analytically tractable theoretical framework to study the optimal supply of central bank reserves when the demand for reserves is uncertain and nonlinear. We fully characterize the optimal supply of central bank reserves and associated market equilibrium. We find that the optimal supply of reserves under uncertainty is greater than that absent uncertainty. With a sufficient degree of uncertainty, it is optimal to supply a level of reserves that is abundant (on the flat portion of the demand curve). The model captures the empirical observation that the variability of interest rate spreads depends on reserves supply.
Keywords: E52; E58; E41; E42; 330; monetary policy implementation; rate control; federal funds rate; Geldmenge; Geldpolitik; Risiko; Theorie